Identification of Aquifer in the MIPA Faculty - University of Jember Using 1D Geoelectrical Resistivity Method with Schlumberger Array - Buwana, Bayu; Priyantari, Nurul; Supriyadi, Supriyadi (Jurnal ILMU DASAR, 2020)
Faculty of Mathematics and Natural Sciences University of Jember located in Sumbersari District with lithological conditions in the form of volcanic rocks, lithosol soils, and regosol soils that are capable of absorbing water and potentially as aquifers. In point of fact, in the campus zona of the University of Jember including in the Faculty of Mathematics and Natural Sciences, there is always a shortage of freshwater for various academic and non-academic activities. Therefore, research needs to be conducted to assess the lithology of subsurface structures in the FMIPA zone so that the depth of groundwater layers and aquifer layers can be determined. The study was conducted using the Schlumberger array geoelectric resistivity method at 5 VES points. The results obtained in the form of resistivity log curves can be seen that at the five points VES has lithology in the form of clay, gravel, sandstone, and groundwater layer. Each VES point was identified the groundwater layer and some of them were identified as aquifers. The aquifer with the greatest thickness is found at point VES 2, which is to the west of the Baitul Ilmi Mosque, so it is recommended as the location of a new well.Keywords: lithology, aquifers, geoelectric resistivity method, groundwater.